Using Information Communication Technology as a Teaching tool in Sudanese Governmental Universities of Khartoum State - Abdalla Eldow; Mohanaad Shakir; Mohamad Yahya Abdullah; Sohail Iqbal Malik (Politeknik Negeri Padang, 2017)
The revolution of Information Technology (IT) and the rapid development in the communications inevitably the Sudanese educational institutions to use the new technology tools in their programs and strategies. Especially there are some private Sudanese universities take the implementations of (ICT) in their account. The main aim of this study is to explore the reasons behind the useless or the effective use of the (ICT) in (SGU) in teaching. The study selected (10%) from the teachers in (SGU) as a sample, such that the sample of teachers after selection is (600) teacher. The questionnaire method was adopted for collection of data in this study, with benefit from (Likert) method. The study founded that (SGU) used some (ICT) hardware, software and tools properly such as: computers, projectors and internet in teaching and in their other academic activities. In addition, there is a middle and rarely usage for other (ICT) such as video conferencing system, virtual meeting system, planning student’s courses, preparing students courses, preparing lectures in presentation software and giving students assignments to be presented by computers. Some of (ICT) tools are not used in (SGU) such as (digital cameras, interactive whiteboards). In addition, the study founded that there is no teacher training in (SGU), in spite of including this activity in the universities plans. The study recommends (SGU) to concern with teacher’s training and other (ICT) tools such as (interactive whiteboards) and (internet speed).